A New Production of an Old Play. Barbarians by M. Gorky on the German Stage of 1990s (Based on Press Materials) - I. V. Tolokonnikova (Концепт: философия, религия, культура, 2024)
The issue of how national cultures are perceived by representatives of other cultures is particularly relevant today considering some communities’ attempts at cancellation against former partners that, until recently, were enthusiastically interested in. Written in 1905 by a prominent Russian and Soviet writer M. Gorky, Barbarians is one example of a work which used to attract attention in the West as a cultural portrait of a country but is now almost forgotten. The article aims to study the semantic dominants of the production, as staged in the theater of Bad Godesberg, Germany, in 1993, by examining it as a representation of Russian culture for German audience. To enable the analysis the following tasks were addressed: 1) to systematize information about the connections of M. Gorky's creative work with German culture; 2) to clarify the place of the play Barbarians in M. Gorky's work in light of its theatrical destiny; 3) to describe the key concepts that form the basis of its poetics; 4) to identify the socio-cultural issues that were represented in the studied German theater production of 1993; 5) to establish the cultural boundaries of perception of Russian culture by the German public of the early 1990s – 2024 in terms of the studied phenomenon. The materials for the study were the original text of the play, its theatrical production in the Kammerspiele Bad Godesberg theater, and publications in German media selected by random sampling. Based on the axiological and hermeneutic approaches, as well as imagology, the author uses the biographical method, and case study method, along with content and literary analyses. As a result, data was obtained on the specifics of the perception of the image of Russian culture in Germany in the early 1990s within the framework of the formation of a theatrical image and its search for little-known details of knowledge of the Russian soul. It is shown that in Germany they tried to associate this image with the important, yet at the same time very ambiguous, concept of barbarism for German culture, showing for the German audience, above all, the vitality of the culture. The author concludes that the German public perceived Maxin Gorky as one of the key representatives of Russian culture. Gorky’s play Barbarians, little known in Russia, was a popular theatrical production in Germany in 1990s due to its conceptual characteristics: in which the mysterious Russian soul is presented through the positive connotations of vitality and hopefulness. This ecology of culture formed the essence of the poetics of Jaroslav Chundela, who realized the creative impulse of M. Gorky in a relevant production that caused wide resonance in German society. The socio-cultural issues of ‘ecology’, in the broad sense, laid the foundation for the expansion of the cultural boundaries of the perception of Russian culture by the German public in the early 1990s, which by 2024 allows us to speak about the limitations of attempts to cancel Russian culture, which remain of universal human value regardless of political situation.